Annual Parasite Incidence Malaria di Kota Bitung tahun 2021-2023 - Cahya Kamila Sugiarta; Oksfriani Jufri Sumampouw; Odi Roni Pinontoan (Universitas Sam Ratulangi, 2024)
Background: Malaria is a life-threatening disease and is mainly found in tropical countries including Indonesia. Malaria is greatly influenced by climate factors such as temperature, humidity, and rainfall. Malaria is spread in subtropical and tropical areas, because in these areas it is very suitable for living and breeding mosquitoes Anopheles and Plasmodium sp. in completing the life cycle in the mosquito's body. Bitung is one of the areas that is suitable for the development of malaria. One of the measures of malaria cases is the annual parasite index (API). The purpose of this study is to calculate the Malaria API in Bitung City in 2021-2023. Methods: This is descriptive quantitative research. This research was carried out in March-July 2024 which took place in Bitung City. The population in this study is all malaria cases in Bitung City in 2021-2023. The research sample is the total population. Malaria case indicator based on API where the number of positive malaria cases divided by the number of at-risk residents in a sub-district in the same time period multiplied by 1,000 residents. The data obtained were then analyzed descriptively. Research Results: The results showed that the 5 sub-districts are found to be in the high-density category (> 500 people/km2), namely Aertembaga, Girian, Madidir, Maesa and Matuari sub-districts. There are 2 sub-districts in medium density (250-500 people/km2), namely North Lembeh and South Lembeh sub-districts. Ranowulu District is in the low-density category (1-249 people/km2). The results of this study show that there are 2 sub-districts included in the medium API, namely North Lembeh (2.42 ‰) and Maesa (3.74 ‰) sub-districts. Only 1 sub-district was found, namely South Lembeh sub-district (15.4 ‰) which was classified as high. Conclusion: The conclusion of this study is that South Lembeh sub-district is in the high category with an API of 15.4 ‰.